Empowering Memory and Movement : Thinking and Working across Borders - Schüssler Fiorenza, Elisabeth, 1938- (Book collections on Project MUSE., 2014)
With Empowering Memory and Movement, Elisabeth Schussler Fiorenza completes a three-volume look across her influential work and career. In Transforming Vision (2011), she drew from decades of pioneering scholarship to offer the contours of a critical feminist hermeneutic. The chapters in Changing Horizons (2013) sketched out a theory of liberation. Now, the consequences for a liberating praxis are elaborated in interviews and essays that chart Schussler Fiorenza's own personal and professional history as these are intertwined with the history of the worldwide movement for emancipation and full equality. Empowering Memory and Movement looks back, but also looks around at challenges and potentialities on the global scene, and looks ahead to an emancipatory future, with a critical and wise engagement with scripture and the interpretive tradition always at the center.